Reject conventional wisdom for a competitive advantage: Don`t swim like Phelps - Havriluk, R. (MIT Sloan Sports Analytics Conference 2016, 2016)
Coaches are generally and justifiably skeptical about scientific information. This presentation will explain how the status quo in technique, training, skill learning, and injury prevention limits performance and how the application of science can produce faster swimming much sooner than by adhering to conventional wisdom.